2011
DOI: 10.1073/pnas.1110552108
|View full text |Cite|
|
Sign up to set email alerts
|

Duplication and partitioning in evolution and function of homoeologous Q loci governing domestication characters in polyploid wheat

Abstract: The Q gene encodes an AP2 -like transcription factor that played an important role in domestication of polyploid wheat. The chromosome 5A Q alleles ( 5AQ and 5Aq ) have been well studied, but much less is known about the q alleles on wheat homoeologous chromosomes 5B ( 5Bq ) and 5D ( 5Dq ). We investigated the organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
130
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(132 citation statements)
references
References 37 publications
2
130
0
Order By: Relevance
“…Therefore, the tetraploid wheat genome mainly contributed to grain shape in synthetic hexaploid wheat. It has been considered that the A genome predominantly controls morphological traits including spike shape, grain shape, and thickness of empty glumes in allopolyploid wheat (Peng et al, 2003;Zhang et al, 2011). The predominant effects of the A genome on wheat morphology might result in limitation of the Dgenome contribution to wheat grain shape.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the tetraploid wheat genome mainly contributed to grain shape in synthetic hexaploid wheat. It has been considered that the A genome predominantly controls morphological traits including spike shape, grain shape, and thickness of empty glumes in allopolyploid wheat (Peng et al, 2003;Zhang et al, 2011). The predominant effects of the A genome on wheat morphology might result in limitation of the Dgenome contribution to wheat grain shape.…”
Section: Discussionmentioning
confidence: 99%
“…The Q gene in wheat was cloned as a homolog of Arabidopsis APETALA2 (Simons et al, 2006). Although the Q genes of CS and LDN have identical coding sequences (Simons et al, 2006;Abdollahi et al, 2012), we found an insertion/ deletion 1.5 kb upstream of the translation initiation site of the Q gene (Zhang et al, 2011; Supplementary Fig. S1).…”
Section: Discussionmentioning
confidence: 91%
“…JF701619) and LDN (acc. JF701620) (Zhang et al, 2011) were aligned using CLC sequence viewer version 6.6.2 (Supplementary Fig. S1).…”
Section: Methodsmentioning
confidence: 99%
“…This formed a stable hexaploid spelt (hulled) wheat, from which a freethreshing derivative was derived by selection. New characteristics such as elastic dough for bread-making were introduced from the A. tauschii genome, with gene dosage effects and pseudogenization contributing to some polyploid-specific traits 58,59 . Genetic diversity in bread wheat was constrained during the domestication of emmer wheat and by the small number of individual plants that contributed to the formation of the new hexaploid bread-wheat species 60 .…”
Section: Domestication Erodes Genetic Diversitymentioning
confidence: 99%